Severe Combined Immunodeficiency: Knowledge and Information Needs Among Healthcare Providers - Kutsa, Oksana; Gwaltney, Angela; Creamer, Alissa; Raspa, Melissa (Frontiers in Pediatrics, 2022)
Background: Severe combined immunodeficiency (SCID) is a group of life-threatening genetic disorders responsible for severe dysfunctions of the immune system. Despite the expansion of newborn screening in the U.S., there are gaps in healthcare providers’ knowledge of SCID. Methods: We recruited 277 U.S. healthcare providers for an online survey. The survey assessed providers’ experience with SCID patients, knowledge about SCID, and needs and preferred sources for SCID-related informational resources. We examined differences between providers who have seen 2 or more patients with SCID (SCID provider group) and those who have seen 0-1 SCID patients (non-SCID provider group). Results: Overall, 210 (75.8%) providers were included in the non-SCID provider group, and 121 (57.6%) of these providers were pediatricians. Compared to the SCID provider group, non-SCID provider group reported lower mean rating of SCID knowledge (x̄=4.8 vs. x̄=8.6, p < .0001) and higher informational needs. The largest informational needs identified by the non-SCID provider group were “understanding specific type of SCID” and “understanding what to expect across the lifespan.” In the SCID provider group, the highest rated informational need was “family support referrals.” Participants in the non-SCID provider group identified scientific publications and websites as preferred sources, with some variation between medical specialties. Conclusion: Based on their experience with treating SCID patients, providers have varying levels of SCID knowledge and different informational needs. For providers who have encountered few SCID patients, informational needs start early, usually immediately after receiving a positive newborn screening result. These findings provide useful direction for the development and preferred outlets for receiving SCID-related information, with some variations between different types of providers. Results from this study will serve as a guide for creating relevant and accessible SCID resources for providers who can utilize them to improve care for SCID patients.